2011
DOI: 10.3382/ps.2011-01430
|View full text |Cite
|
Sign up to set email alerts
|

Does early antipredator training increase the suitability of captive red-legged partridges (Alectoris rufa) for releasing?

Abstract: This study aimed to evaluate the postrelease survival and spatial distribution of farm-bred red-legged partridges (Alectoris rufa) that were subject to a prerelease training program based on exemplary behavior and alarm calls given by adults that acted as experienced demonstrators in simulated predator encounters (wooden raptor models and humans). Two groups of partridges were released in this study: trained (intensively reared birds accompanied by tutors) and control (chicks reared without tutors). Releases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 43 publications
1
31
0
6
Order By: Relevance
“…; Gaudioso et al. ; Carthey and Banks ). To our knowledge, prerelease training has not been shown to reduce postrelease survival in prey species exposed to exotic predators.…”
Section: Why Predator Avoidance Training Involving Simulated Encountementioning
confidence: 99%
See 1 more Smart Citation
“…; Gaudioso et al. ; Carthey and Banks ). To our knowledge, prerelease training has not been shown to reduce postrelease survival in prey species exposed to exotic predators.…”
Section: Why Predator Avoidance Training Involving Simulated Encountementioning
confidence: 99%
“…Indeed, most practitioners investigating the utility of prerelease predator training have used evidence of a prerelease change in behavior of trained individuals rather than a difference in postrelease survival of trained and untrained individuals as a measure of success (Miller et al 1990;H€ olzer et al 1995;McLean et al 1996;Moseby et al 2012). Of particular note is that studies reporting improved survival of trained captive-bred animals after release invariably involve a response to native predators rather than to exotic species (White et al 2005;Gaudioso et al 2011;Carthey and Banks 2014). To our knowledge, prerelease training has not been shown to reduce postrelease survival in prey species exposed to exotic predators.…”
Section: Why Predator Avoidance Training Involving Simulated Encountementioning
confidence: 99%
“…The provision of raised perches in early life facilitates the development of elevated roosting at dusk and the associated morphology, resulting in enriched birds being more likely to roost off the ground and predated upon less (Santilli and Bagliacca 2017;Whiteside et al 2016). Anti-predator training via the presentation of predator stimuli in early life influenced vigilance behaviour with captive-reared grey partridge, Perdix perdix (Beani and Dessì-Fulgheri 1998), and improved post-release survival of red-legged partridges Alectoris rufa and chuckar Alectoris chuckar (Gaudioso et al 2011;Slaugh et al 1992). Provision of a more complex and varied diet early in life can alter the foraging behaviour of reared pheasants, meaning that they exploit a wider natural diet, process prey more effectively, spend more time being vigilant and less time in exposed areas and subsequently survive better (Whiteside et al 2015).…”
Section: Mitigation That May Reduce Predationmentioning
confidence: 99%
“…Red-legged partridges, reared in commercial game farms, showed differences in their escape reaction which can explain the low ability of these birds to survive in the wild (Pèrez et al, 2010). Gaudioso et al (2011) showed that subjecting captivereared red-legged partridges to an anti-predator training improves their ability to survive after release. The beneficial effect of semi-natural rearing methods was also shown in the pheasant (Phasianus colchicus) resulting in an improved survival and/or breeding success (Brittas et al, 1992;Ferretti et al, 2011) It is of interest that the only artificially-reared radiotagged partridge which survived after the breeding season spent the winter time in a group formed by Natural reared birds.…”
Section: Discussionmentioning
confidence: 99%